2015
DOI: 10.3923/ijaef.2015.25.32
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure and Firm Performance of Listed Non-Financial Companies in Bangladesh

Abstract: This study investigates the firm performance on capital structure for the listed non-financial companies in Dhaka Stock Exchange (DSE) for the period of 2008-2011 under judgment sampling method. Specific objective of this research is to examine the relationship between the attribute of capital structure and the performance as measured by Return On Assets (ROA) and Return On Sales (ROS). Multiple regression models were used to estimate the influence of capital structure on firm performance and capital structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
1
14
0
2
Order By: Relevance
“…Hermuningsih (2013) found that a company manager could choose using debt ratios to increase the company's value. Meanwhile, the Modigliani-Miller model suggests that companies will be able to increase their value by using debt, and one of the reasons is the taxa- http://dx.doi.org/10.21511/imfi.17 (1).2020. 15 tion aspect (Margaretha & Rizki, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hermuningsih (2013) found that a company manager could choose using debt ratios to increase the company's value. Meanwhile, the Modigliani-Miller model suggests that companies will be able to increase their value by using debt, and one of the reasons is the taxa- http://dx.doi.org/10.21511/imfi.17 (1).2020. 15 tion aspect (Margaretha & Rizki, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that longterm debts are likely to impose heavy terms and conditions and costly to finance in Bangladesh. The negative relationship between firm performance and leverage ratios is also recorded in the study of Rouf (2015). Another empirical study in Bangladesh done by Meah (2019) found that larger corporate boards, larger audit committees, and foreign investors reduce the flow of debt in firms and make firms less risky.…”
Section: Bangladesh Perspectivementioning
confidence: 77%
“…Where, β, Ȥ, λ represent the intercepts of the equations; ε is the random error term; i represents the firms and t represents the periods, 2013, 2014, 2015, 2016and 2017 Table 3 documents the summary of the variables used in this paper: Table 4 represents the descriptive statistics of mean, minimum and maximum values of dependent variable ROA for family and non-family firms and the amount of data are 390 firm-years for a period of 2013 to 2017 in a row. It is shown in the table that the average ROAs for family firms and non-family firms in Bangladesh are 10.91 percent and 9.82 percent respectively.…”
Section: Research Modelsmentioning
confidence: 99%
“…Consequently, a company increases its profitability and enjoys higher turnover (Ramli, Latan, & Solovida, 2019;Rub, 2012). A negative impact of debt-to-equity ratio on financial performance occurs when the company borrows funds at a high interest rate, resulting in financing costs that are more than the company's profits (Rouf, 2015;Pratheepkanth, 2011).…”
Section: Other Determinants Of Financial Performancementioning
confidence: 99%
“…Moreover, larger companies are likely to receive higher credit limits and longer credit periods than smaller companies, which result in lower business costs and higher profits, which means better turnover. Consequently, the size of a firm has a significant positive impact on financial performance (Eljelly, 2004;Bibi & Amjad, 2017;Rouf, 2015). Inflation is another factor that has emerged as wielding a significant impact on financial performance.…”
Section: Other Determinants Of Financial Performancementioning
confidence: 99%